2021
DOI: 10.3389/fphys.2021.744219
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Novel Gene Correlated With Vascular Smooth Muscle Cells Proliferation and Migration in Chronic Thromboembolic Pulmonary Hypertension

Abstract: Objective: Chronic thromboembolic pulmonary hypertension (CTEPH) is characterized by thrombofibrotic obstruction of the proximal pulmonary arteries, which result in vascular remodeling of the distal pulmonary artery. While the cellular and molecular mechanisms underlying CTEPH pathogenesis remain incompletely understood, recent evidence implicates vascular remodeling. Here, we identify the molecular mechanisms that contribute to vascular remodeling in CTEPH.Methods: Microarray data (GSE130391) for patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 43 publications
(52 reference statements)
0
6
0
Order By: Relevance
“…p = 0.0008), but upregulated in CTEPH (Log 2 FC = 2.99, adj. p = 0.0003) as Wang et al reported (19). Family with sequence similarity 114 member A1 (FAM114A1) was downregulated in IPAH (Log 2 FC = −1.03, adj.…”
Section: Identification and Comparison Of Degs Between Ipah And Ctephmentioning
confidence: 66%
See 4 more Smart Citations
“…p = 0.0008), but upregulated in CTEPH (Log 2 FC = 2.99, adj. p = 0.0003) as Wang et al reported (19). Family with sequence similarity 114 member A1 (FAM114A1) was downregulated in IPAH (Log 2 FC = −1.03, adj.…”
Section: Identification and Comparison Of Degs Between Ipah And Ctephmentioning
confidence: 66%
“…Increased FOS expression in primary PASMCs from patients with CTEPH was reported to be associated with excessive proliferation and migration of PASMCs (19). Consistently, FOS inhibitors attenuated TNF-α induced proliferation and migration in human PASMCs (19). Meanwhile, to find out the common mechanisms and hub genes involved in PA remodeling in PH, we screened 22 hub DEGs and verified the top 10 common DEGs by using hypoxia with Sugen-induced PAH rats.…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations